Nexus between food insecurity, poverty, and climate change: a cross-regional multifactorial analysis - Dossa, Kossivi Fabrice; Miassi, Yann Emmanuel (Frontiers in Environmental Economics, 2025)
Climate change, by exacerbating poverty and food insecurity, creates complex dynamics that threaten global food security. This study aims to examine the complex interactions between these phenomena (climate change, poverty and food security), adopting a multidimensional approach to understand their direct and indirect relationships. The study focused on eight countries representing the African, Asian, American and European continents, selected according to their Human Development Index (HDI). Data is collected for the period 1990–2020 from platforms such as FAO, World Bank, UNDP and Our World in Data, based on indicators of poverty, climate change and food insecurity (qualitative approach). Data analysis is based on time series (temporal evolutions in climate and poverty variables) as well as thematic content analysis. Analysis of evolutions in poverty indicators and the HDI reveals marked disparities between regions, with notable progress in Asia and Europe, but persistent challenges in Africa and Yemen. Similarly, these disparities are also observed for climate evolutions and changes in land, particularly in Africa and Asia. Regarding food insecurity evolutions, there is a considerable increase with marked regional disparities, where Africa and Latin America are the most affected. Direct arable effects include reduced agricultural productivity, crop and livestock yield, increased undernourishment, reduced livelihoods and producer incomes. Indirectly, these changes reduce crop quality, disrupt ecosystem services, exacerbate resource conflicts and increase production costs. These findings provide guidance for policymakers and researchers in developing integrated strategies that address not only food security and poverty, but also climate change.